Using factorial analysis for validating a maturity measurement instrument in open innovation - Rocha, Giseli Valentim; Mello, Carlos Henrique Pereira; Paiva, Anderson Paulo de; Pereira, Tabata Fernandes; Turrioni, Joao Batista (Acta Scientiarum. Technology, 2019)
Open innovation (OI) has taken its place as a mainstream innovation process. Although the growing interest in OI since then, there are still many unanswered questions. One of the most persistent for researchers alike relates to how OI can be measured: what framework could companies adopt to measure OI? What are the most important constructs to be considered in the definition of a framework for OI? We identify constructs to be considered in a framework for the maturity measurement in medium and large companies in Brazil, considering strategic, organizational and operational aspects. The purpose of this paper is to develop an OI measurement instrument that has sound psychometric properties and recognize a key feature on the field. The results suggest that the constructs have good empirical support. In the manner in which the instrument is presented, it is possible to separately measure construct related to each of the approaches.